Expression of microRNA‐155 in inflammatory cells modulates liver injury. Issue 2 (2nd May 2018) - Blaya, Delia; Aguilar‐Bravo, Beatriz; Hao, Fengjie; Casacuberta‐Serra, Silvia; Coll, Mar; Perea, Luis; Vallverdú, Júlia; Graupera, Isabel; Pose, Elisa; Llovet, Laura; Barquinero, Jordi; Cubero, Francisco Javier; et al.
Abstract : MicroRNA 155 (miR‐155) is involved in immune and inflammatory diseases and is associated with liver fibrosis and steatohepatitis. However, the mechanisms involved in miR‐155 regulation of liver injury are largely unknown. The role of miR‐155 in acute liver injury was assessed in wild‐type (WT), miR‐155 −/−, and miR‐155 −/− mice transplanted with WT bone marrow. Additionally, miR‐155 expression was evaluated in liver tissue and peripheral blood mononuclear cells of patients with autoimmune hepatitis. Concanavalin A, but not acetaminophen, treatment increased the expression of miR‐155 in liver tissue of WT mice. Concanavalin A induced increases in cell death, liver aminotransferases, and expression of proinflammatory cytokines (chemokine [C‐X‐C motif] ligands 1, 5, 9, 10, and 11; chemokine [C‐C motif] ligands 2 and 20; and intercellular cell adhesion molecule 1) in miR‐155 −/− compared to WT mice. Importantly, these animals showed a significant decrease in cluster of differentiation 4–positive/chemokine (C‐X‐C motif) receptor 3–positive and forkhead box p3–positive cell recruitment but no changes in other inflammatory cell populations. Mechanistically, miR‐155‐deficient regulatory T cells showed increased SH2 domain–containing inositol 5‐phosphatase 1 expression, a known target of miR‐155. Inhibition of SH2 domain–containing inositol 5‐phosphatase 1 in miR‐155 −/− mice restored forkhead box p3 recruitment and reduced liver cytokine expression. Transplantation of bone marrow from WT animals into miR‐155 −/− mice partially reversed the effect of concanavalin A on miR‐155 −/− mice as assessed by proinflammatory cytokines and cell death protein expression. Patients with autoimmune hepatitis showed a marked increase in miR‐155 expression in the liver but reduced expression of miR‐155 in peripheral blood mononuclear cells. Conclusion: miR‐155 expression is altered in both liver tissue and circulating inflammatory cells during liver injury, thus regulating inflammatory cell recruitment and liver damage; these results suggest that maintaining miR‐155 expression in inflammatory cells might be a potential strategy to modulate liver injury. (Hepatology 2018).